2020
DOI: 10.1007/s00774-020-01173-3
|View full text |Cite
|
Sign up to set email alerts
|

Incidence rate of vitamin D deficiency and FGF23 levels in 12- to 13-year-old adolescents in Japan

Abstract: Introduction The incidence rate of vitamin D deficiency is increasing throughout the world. We measured the incidence rate of vitamin D deficiency and fibroblast growth factor 23 (FGF23) levels in 12-to 13-year-old adolescents in Japan. Materials and methods A total of 492 adolescents (247 boys and 245 girls) from Japanese community enrolled in this study. 25 hydroxyvitamin D (25(OH)D) was measured with radioimmunoassay. In the subjects with low 25(OH)D levels (≦ 20 ng/ ml), intact parathyroid hormone (iPTH), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 47 publications
1
2
0
Order By: Relevance
“…In consist with previous studies, we confirmed that 25(OH)D is associated with the serum level of calcium ( 29 ) and PTH ( 30 ). Low level of 25(OH)D is usually related to the clinical symptoms of vitamin D deficiency ( 31 ).…”
Section: Discussionsupporting
confidence: 92%
“…In consist with previous studies, we confirmed that 25(OH)D is associated with the serum level of calcium ( 29 ) and PTH ( 30 ). Low level of 25(OH)D is usually related to the clinical symptoms of vitamin D deficiency ( 31 ).…”
Section: Discussionsupporting
confidence: 92%
“…There are limited data about mineral metabolism variables in healthy children due to the complexity of the sample that involves changes inherent to growth and development and the difficulties involved in studies in the pediatric population compared to the adult population (difficulties in recruiting a large number of healthy participants and issues in collecting adequate blood volumes, particularly from very young children). Table 1 provides information on calcium, phosphate, PTH, vitamin D metabolites, FGF23 and Klotho in healthy children on the basis of published findings meeting the necessary criteria to be considered as reference laboratory values [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ].…”
Section: Circulating Variables Linked To Mineral Metabolism_reference...mentioning
confidence: 99%
“…Despite the metabolic connection between FGF23 and vitamin D, little is known about the status of FGF23 and Klotho in individuals with rickets induced by vitamin D deficiency. A study in 492 healthy Japanese adolescents found that 28% are vitamin D deficient and there is no significant correlation between serum concentrations of 25OHD and FGF23 [ 21 ]. In contrast, Kubota et al [ 49 ] found low serum FGF23, less than 19 pg/mL, in patients with vitamin-D-deficient rickets.…”
Section: Fgf23 and Vitamin D Metabolismmentioning
confidence: 99%